Kepemimpinan Kiai dalam Mengembangkan Wirausaha Santri di Pondok Pesantren At Tahdzib Jombang - Nurul Indana; Asyrof Syafi'i; pengelola, pengelola (TABYIN: JURNAL PENDIDIKAN ISLAM, 2023)
Islamic boarding schools, in its development, do not only provide religious education. Islamic boarding schools also provide entrepreneurial provisions to their students. The provision of entrepreneurial provisions is intended so that alumni can contribute to job creation in addition to having the ability in the religious field as a means of da'wah. Likewise with the at-tahdzib Islamic boarding school Ngoro Jombang. The thoriqoh-based boarding school equips students with entrepreneurial knowledge. This study uses literature research. There are three data collection techniques used; interview, observation and documentation. Meanwhile, the activities in the analysis includedata reduction,data display, andconclusion drawing verification. While the technique for checking the credibility of the data was carried out using technical and triangulation of sources . Meanwhile, there are four strategies implemented to develop student entrepreneurship, namely the introduction of the business world according to Islam, channeling entrepreneurial knowledge to students, implementing entrepreneurial knowledge by doing business and the last is evaluating the student entrepreneurship program